Pengaruh Model Pembelajaran Problem Based Learning Berbantuan Software Simurelay terhadap Kompetensi Siswa pada Mata Pelajaran Instalasi Motor Listrik - Muhammad Rizky Ardiansyah; Fendi Achmad; Ali Nur Fathoni; M. Syariffuddien Z (Educational Journal, 2026)
This study examined the effect of the Problem Based Learning (PBL) model assisted by Simurelay software on students' competence in the Electric Motor Installation course among eleventh-grade Electrical Power Installation Engineering students at SMK Negeri 1 Sidoarjo. A quasi-experimental method with a nonequivalent control group pretest-posttest design was used, involving 36 students in the experimental class (PBL assisted by Simurelay) and 37 students in the control class (direct instruction). Data were collected using a 25-item multiple-choice test for the knowledge aspect and an observation sheet for the skill aspect, then analyzed through normality, homogeneity, N-Gain, and independent sample t-test procedures. Both instruments were rated highly valid (100% expert validation) and reliable (Cronbach's alpha of 0.834 for knowledge and 0.827 for skill). The experimental class obtained a higher mean N-Gain (0.713, high category) than the control class (0.686, moderate category). The independent sample t-test showed significant effects for both the knowledge aspect (Sig. = 0.005) and the skill aspect (Sig. = 0.040), both below 0.05. It is concluded that the PBL model assisted by Simurelay software significantly improves students' competence in Electric Motor Installation compared with direct instruction.